PEMODELAN PELENGKUNG BETON BERTULANG DENGAN MEMPERHITUNGKAN INTERAKSI TANAH DAN STRUKTUR (KASUS: ALTERNATIF RENCANA JEMBATAN SERANGAN – TANJUNG BENOA) - Laintarawan, I Putu; Sukrawa, I Made; Sudarsana, I Ketut (Jurnal Ilmiah Teknik Sipil, 2012)
The Serangan-Tanjung Benoa Bridge is designed as a reinforced concrete arch bridge as it usually built on hard soils, so it can be modelled as a fixed arch. However, the brigde was design on soft soil (N < 15) with hard soil (N > 50), 30 m below. Therefore, it is necessary to study the behavior of arch structure considering soil-structures interaction, due to vertical and lateral loads. Two models were made in order to model the soil-structure interaction: Model 1, the lateral soil supports is modelled as spring; Model 2, soil and foundation are modelled as solid element. Model 3, fixed arch was modelled without foundation. While modelling the soil as spring and solid, pile groups were asssumed as caisson and were modelled as solid, and the elastic modulus of soil between piles is equal to the elastic modulus of pile and its values were varieted and compared to the fixed model. Modulus of base soil lateral reaction, kh is modeled as spring with E of 28 N and uniformly distributed on caisson surface area behind the load. The finite element method was made in 3D using SAP2000 program with static and time history analysis for vertical and earthquake load, respectively. Soil modelled as spring and solid element in soil-structure interaction show compatible, in which the deformation and internal forces varied by less than 2%. The maximum deflection occurred on the peak of arch due to dead load of 191.4 mm, or 37.87% smaller than the maximum deflection of the model including soil-structure interaction. Moreover, fixed arch model has natural period of 2.37 second, which is 0.39 second shorter than that including soil-structure interaction. With E greater than 9000 MPa (sandstone type) the three models give deformation and internal forces it compatible values with differences less than 2.2%.
Keywords: arch bridge, soil-structure interactions, finite element model